Comparison of effectiveness and safety of high-power vs. conventional-power radiofrequency ablation for treatment of atrial fibrillation - Cui, Penghui; Qu, Yunpeng; Zhang, Jichang; Wu, Junduo; Zhang, Jing; Shi, Yongfeng; Liu, Bin (Frontiers in Cardiovascular Medicine, 2022)
Aim To compare high-power (HP) vs. conventional-power (CP) radiofrequency ablation for atrial fibrillation (AF). Methods We retrospectively enrolled AF patients undergoing CP (30–40 W, 43 patients) or HP (50 W, 49 patients) radiofrequency ablation. Immediate pulmonary vein (PV) single-circle isolation, PV-ablation time, AF recurrence, AF recurrence-free survival, and complications were analyzed. Results Diabetes was more common in the CP group than in the HP group (27.91% vs. 10.20%, P = 0.029). The left PV single-circle isolation rate (62.79% vs. 65.31%), right PV single-circle isolation rate (48.84% vs. 53.06%), and bilateral PV single-circle isolation rate (32.56% vs. 38.78%; all P > 0.05) did not differ between the groups. Single-circle ablation times for the left PVs (12.79 ± 3.39 vs. 22.94 ± 6.39 min), right PVs (12.18 ± 3.46 vs. 20.67 ± 5.44 min), and all PVs (25.85 ± 6.04 vs. 45.66 ± 11.11 min; all P < 0.001) were shorter in the HP group. Atrial fibrillation recurrence within 3 months (13.95% vs. 18.37%), at 3 months (11.63% vs. 8.16%), and at 6 months after ablation (18.60% vs. 12.24%; all P > 0.05) was similar in both groups. Atrial fibrillation recurrence-free survival did not differ between the groups (Kaplan-Meier analysis). Cardiac rupture and pericardial tamponade did not occur in any patient. Pops occurred in 2 and 0 patients in the HP and CP groups, respectively (4.08% vs. 0.00%, P = 0.533). Conclusion High-power ablation improved operation time and efficiency without increasing complications.